PERTIMBANGAN HAKIM DALAM PEMIDANAAN PELAKU TINDAK PIDANA PEMBUNUHAN (Studi Kasus Putusan Nomor. 104/Pid.B/2016/PN.Gst) - Yuniar Hati Laia (Jurnal Panah Hukum, 2022)
The judge's consideration in trying and deciding a criminal case is very important in ending the trial. This study aims to determine and analyze the judge's considerations in convicting the perpetrators of the crime of murder (case study decision number 104/Pid.B/2016/PN.Gst). This research is a normative research with data collection techniques using secondary data. The secondary data obtained in this study, the authors then analyzed using qualitative analysis methods which were then described into a general conclusion which would be completed by the author in the form of research results or thesis. Based on the results of the research findings and discussion in the judge's consideration in convicting the perpetrators of the crime of murder (case study decision number 104/Pid.B/2016/PN.Gst), it can be concluded that the primary charge was not fulfilled because the element of whoever deliberately planned in advance which results in the loss of a person's life, the imposition of a sentence of 12 (twelve) years on the perpetrator is appropriate because the legal considerations have been based on juridical considerations and non-juridical considerations. As for the advice, it is better for the prosecutor and judge in prosecuting both examining and adjudicating a criminal case to still uphold the values ​​of justice to create a legal order that is in accordance with the objectives of the state as a state of law